Water-based adhesive for wood and bamboo
Patent Information
- Application Number
- JP2023123336
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-05-23
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2043-07-28
Smart Images

Figure 0007641036000001 
Figure 0007641036000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a type of adhesive, especially a water-based adhesive for application on wood and bamboo. [Background technology]
[0002] Traditionally, adhesives used for wood and bamboo have been made from petrochemicals such as phenol, urea, melamine, and formaldehyde. Adhesives made from these petrochemical raw materials or their derivatives often offer excellent adhesion, mechanical strength, temperature resistance, and water resistance, and are low-cost and affordable, making them difficult to replace due to their many advantages. However, as environmental awareness has risen and people have become more concerned about their health, the disadvantages of adhesives made from petrochemicals have become apparent.
[0003] Due to the good reactivity of formaldehyde, urea formaldehyde resin adhesives containing formaldehyde usually have the advantages of high adhesive strength, good heat resistance, and good water resistance. Currently, more than 80% of adhesives applied to wood and bamboo still use urea formaldehyde adhesives, but formaldehyde has been proven to be a toxic substance that can cause carcinosis in humans. Furthermore, wood and bamboo that use adhesives containing formaldehyde are used in various furniture, interior building materials, interior decorations, etc., and the formaldehyde emission cycle in these products can last for 10 to 15 years.
[0004] Regulations on the content of formaldehyde, a carcinogenic risk, are becoming increasingly strict in countries around the world, so one clear goal is to develop new forms of formaldehyde-free adhesives that can improve the sustainability of the ecological environment and reduce risks to the human body.
[0005] Formaldehyde-free biomass adhesives are adhesives that do not use formaldehyde, but also incorporate biomass materials. In recent years, soy protein, lignin, starch, and tannins are biomass materials that are often used as wood adhesives. However, they have shortcomings such as weak adhesive strength and poor water resistance, and are not yet widely used in commercial applications. Among them, soy protein began to be used for wood adhesion in the 1930s, but its low adhesive strength has been criticized as a drawback. Although related improvements were disclosed in U.S. Patent Publication No. US9493693, when actually applied commercially, there are still problems such as high heating temperature, long time, and high energy consumption. In addition, soy protein has problems in that it is difficult to process in practice, making it difficult for workers to adapt.
[0006] In addition, although lignin and tannin are structurally stable, they also have low reactivity, and chemical modification is usually required to increase their reactivity. Furthermore, lignin itself contains phenol functional groups, and is often added to phenolic resins, but its disadvantages include poor reactivity, high reaction temperature, and poor water resistance. Starch is a natural polymer that is often used as a food additive, and hydrogen bonds are its main function, but the function of hydrogen bonds is much weaker than that of general chemical reaction covalent bonds. Starch is used as an adhesive, but its water resistance and adhesive strength are weak. Although the covalent bonds of chemical reactions have been increased by modifying starch, its water resistance and compatibility still do not meet the needs of commercialization. Summary of the Invention [Problem to be solved by the invention]
[0007] According to the shortcomings of the prior art, the present invention mainly provides a water-based adhesive that can be applied to wood or bamboo, introduces natural and renewable raw materials, effectively reduces the dependency on petrochemical products, and improves the sustainability of related industries. [Means for solving the problem]
[0008] The objective of the present invention is to provide a water-based adhesive that can be applied to wood or bamboo, the raw material of which is natural latex made from biomass, blended with environmentally friendly non-toxic water-soluble polymer, and further mixed with a suitable hardener, such as isocyanate or quaternary ammonium salt polymer, which can provide wood and bamboo with good water resistance, adhesive strength and mechanical strength.
[0009] The objective of the present invention is to provide an adhesive that can be applied to wood and bamboo, which is composed of a base agent and a hardener. The base agent includes water-soluble polymers, synthetic rubber latex, and natural latex. The hardener is an isocyanate compound or its polymer, or an aqueous solution of a quaternary ammonium salt polymer.
[0010] In order to achieve the above object, the present invention discloses an aqueous adhesive applicable to wood or bamboo, which comprises a base material consisting of a water-soluble polymer, a synthetic rubber latex and a natural latex, and a curing agent selected from an isocyanate or a quaternary ammonium salt polymer. The weight ratio of the base material to the curing agent is 200:1 to 1:1. The water-soluble polymer is polyvinyl alcohol, which accounts for 2-30% by weight of the total solid content of the base material. The synthetic rubber latex is selected from the group consisting of styrene butadiene rubber latex and styrene butadiene rubber latex containing a carboxylic acid functional group, and the synthetic rubber latex accounts for 2-60% by weight of the total solid content of the base material. The natural latex accounts for 5-90% by weight of the total solid content of the base material.
[0011] In a preferred embodiment of the present invention, the weight ratio of the base agent to the curing agent is from 100:1 to 10:3.
[0012] In a preferred embodiment of the present invention, the water-soluble polymer comprises 3 to 25 weight percent of the total solids of the base.
[0013] In a preferred embodiment of the present invention, the water-soluble polymer comprises 5 to 25 weight percent of the total solids of the base.
[0014] In a preferred embodiment of the present invention, the water-soluble polymer comprises 10 to 25 weight percent of the total solids of the base.
[0015] In a preferred embodiment of the present invention, the hydrolysis mol % of the water-soluble polymer in the base material is 70 to 99.8%.
[0016] In a preferred embodiment of the present invention, the hydrolysis mol % of the water-soluble polymer in the base material is 80-99.8%.
[0017] In a preferred embodiment of the present invention, the hydrolysis mol % of the water-soluble polymer in the base material is 85-99.5%.
[0018] In a preferred embodiment of the invention, the synthetic rubber latex comprises 3 to 55 weight percent of the total solids of the base material.
[0019] In a preferred embodiment of the present invention, the synthetic rubber latex comprises 3 to 40 weight percent of the total solids of the base material.
[0020] In a preferred embodiment of the present invention, the synthetic rubber latex comprises 3 to 30 weight percent of the total solids of the base material.
[0021] In a preferred embodiment of the invention, the natural latex comprises 5 to 85 weight percent of the total solids of the base material.
[0022] In a preferred embodiment of the invention, the natural latex comprises 5 to 75 weight percent of the total solids of the base material.
[0023] In a preferred embodiment of the invention, the natural latex comprises 10 to 60 weight percent of the total solids of the base material.
[0024] In a preferred embodiment of the present invention, the natural latex is obtained from a plant, which also includes epoxidized natural latex or deproteinized natural latex.
[0025] In a preferred embodiment of the present invention, the isocyanate comprises one or more isocyanates, the isocyanate being a compound or polymer thereof that contains an isocyanate functional group.
[0026] In a preferred embodiment of the present invention, the quaternary ammonium salt polymer comprises one or more quaternary ammonium salt polymers, and the quaternary ammonium salt polymer is a polyaminoamide-epichlorohydrin resin (PAE).
[0027] In a preferred embodiment of the present invention, the composition further comprises an inorganic or organic filler, wherein the inorganic filler is selected from at least one or a combination of calcium carbonate, magnesium carbonate, talc, barium sulfate, kaolin, titanium dioxide, silicon oxide, aluminum oxide, and glass fiber, and the organic filler is selected from at least one or a combination of starch, lignin, tannin, cellulose, sugar, and wood flour.
[0028] In a preferred embodiment of the present invention, further adjuvants such as antifoaming agents, thickening agents, thixotropic agents, antioxidants, dispersants, flame retardants, etc. are included. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] In one embodiment, the present invention provides a water-based adhesive for use on wood or bamboo, the water-based adhesive comprising a base agent and a hardener, the base agent being comprised of a water-soluble polymer, a synthetic rubber latex, and a natural latex, the hardener being selected from an isocyanate or a quaternary ammonium salt polymer. The weight ratio of the base agent to the curing agent is 200:1 to 1:1. The water-soluble polymer is polyvinyl alcohol and accounts for 2-30% by weight of the total solids of the base agent. The synthetic rubber latex is selected from the group consisting of styrene butadiene rubber latex and styrene butadiene rubber latex containing carboxylic acid functional groups, the synthetic rubber latex accounts for 2-60% by weight of the total solids of the base agent. The natural latex accounts for 5-90% by weight of the total solids of the base agent. In one embodiment, the weight ratio of the base agent to the curing agent may range from 100:1 to 10:3.
[0030] The raw material natural latex used in the present invention is natural latex derived from plants. The chemical structure of natural latex consists of a high molecular weight polymer mainly composed of isoprene, and is dispersed in water in the form of latex. The natural latex used in the present invention can be used immediately without artificial chemical modification. Natural latex has excellent hydrophobicity, and forms a polymeric rubber film material with excellent water resistance after removing water during use. When applied to an adhesive, the water resistance of an adherend can be significantly improved. A drawback of natural latex is its low stability, and in one embodiment, ammonia water, potassium hydroxide, or a chelating agent may be added as a stabilizer. In one embodiment, 0.1 to 1 weight percent ammonia water may be added to the aqueous solution of natural latex as a stabilizer and bacteriostatic agent.
[0031] If the proportion of natural latex in the base of the present invention is too low, the significance of adding biomass to improve environmental sustainability is lost, and conversely, if too much is added, the water tends to evaporate slightly, making the natural latex more likely to crust and difficult to apply. In one embodiment, the natural latex accounts for 5 to 85 weight percent of the total solids of the base. In one embodiment, the natural latex accounts for 5 to 75 weight percent of the total solids of the base. In one embodiment, the natural latex accounts for 10 to 60 weight percent of the total solids of the base.
[0032] In one embodiment, the natural latex of the present invention includes epoxidized natural latex or deproteinized natural latex. Epoxidized natural latex forms epoxy functional groups on double bonds of molecular chains through chemical reaction, improving reactivity, increasing crosslinking strength, and improving heat resistance, water resistance, and mechanical strength of adhesive force. Deproteinized natural latex removes protein components in latex, which can reduce the probability of mold spoilage.
[0033] The water-soluble polymer in the present invention is polyvinyl alcohol. The addition of the water-soluble polymer promotes the reactivity with the curing agent, improving adhesion and water resistance. In one embodiment, the hydrolysis mol% of the water-soluble polymer is 80 to 99.8%. In one embodiment, the hydrolysis mol% of the water-soluble polymer is 85 to 99.5%. In the present invention, if the hydrolysis rate is too low, the reactivity decreases, and the strength decreases accordingly. In one embodiment, the water-soluble polymer accounts for 3 to 25% by weight of the total solid content of the base agent. In one embodiment, the water-soluble polymer comprises 5 to 25% by weight of the total solid content of the base material. In one embodiment, the water-soluble polymer accounts for 10 to 25% by weight of the total solid content of the base material.
[0034] The synthetic rubber latex, which is the base material of the present invention, can promote reactivity with a curing agent and improve adhesion and water resistance. In one embodiment, the synthetic rubber latex of the present invention accounts for 3 to 55% by weight of the total solid content of the base material. In one embodiment, the synthetic rubber latex accounts for 3 to 40% by weight of the total solid content of the base material. In one embodiment, the synthetic rubber latex accounts for 3 to 30% by weight of the total solid content of the base material.
[0035] The curing agent of the present invention mainly serves to carry out a crosslinking reaction with the base resin. In one embodiment, the isocyanate includes one or more isocyanates, and the isocyanate is a compound containing an isocyanate functional group (isocyanate) or a polymer thereof. In one embodiment, the isocyanate may be diphenylmethane diisocyanate (MDI), including three isomers of 2,2'-MDI, 2,4'-MDI, and 4,4'-MDI, as well as its oligomer (crude MDI or polymeric MDI). In one embodiment, the isocyanate may be toluene diisocyanate tolylene -2,4- tolylene -2,6- diisocyanate (TDI) and its isomers. In one embodiment, the isocyanate may be dicyclohexylmethane diisocyanate (4,4'-diisocyanato-dicyclohexylmethane, H12MDI) and its isomers. In one embodiment, the isocyanate may also be hexamethylene diisocyanate (HDI) and its isomers. In one embodiment, the isocyanate may be isophorone diisocyanate (IPDI). In one embodiment, the isocyanate may be 3,3'-dimethylbiphenyl-4,4'-diisocyanate o-Tolidine diisocyanate (TODI).
[0036] The curing agent of the present invention may also be a quaternary ammonium polymer or may be composed of one or more quaternary ammonium polymers. In one embodiment, the quaternary ammonium salt polymer may be a quaternary ammonium salt polymer (polyaminoamide epichlorohydrin, PAE) formed from the reaction of polyamidoamine with epichlorohydrin. The polymer has a structure represented by formula 1, where n is an integer, and in a preferred embodiment of the present invention, the quaternary ammonium salt polymer comprises one or more quaternary ammonium salt polymers, and the quaternary ammonium salt polymer is a polyaminoamide-epichlorohydrin resin (PAE). Its formula is formula (1): Formula (1) JPEG0007641036000001.jpg37145
[0037] In one embodiment, the composition further comprises an inorganic or organic filler, the inorganic filler being calcium carbonate, magnesium carbonate, talc, barium sulfate, kaolin, titanium dioxide, silicon oxide, aluminum oxide or glass fiber, and the organic filler being starch, lignin, tannin, cellulose, sugar or wood flour.
[0038] In one embodiment, the base agent of the present invention can be added with auxiliary agents including defoamers, thickeners, thixotropic agents, antioxidants, dispersants, flame retardants, etc., to further meet the requirements of the manufacturing process. Alternatively, the base agent of the present invention can be added with inorganic or organic fillers to meet additional requirements for different properties, such as increasing the solid content of the adhesive, improving opacity, and reducing costs. Here, the inorganic fillers include calcium carbonate, magnesium carbonate, talc, barium sulfate, kaolin, titanium dioxide, silicon oxide, aluminum oxide, or glass fiber. The organic fillers include starch, lignin, tannin, cellulose, sugar, or wood flour.
[0039] The present invention will be described below with reference to examples and comparative examples.
[0040] [Example 1] Take 10 grams of polyvinyl alcohol (PVA) aqueous solution (BP-05, 30% by weight, Changchun synthetic resin), add 20 grams of styrene butadiene rubber (SBR) resin (LBT04, Shenfeng special application materials), mix well and evenly, then add 50 grams of natural latex (60% by weight, made in Thailand) and stir evenly to complete the base of the water-based adhesive. Diphenylmethane diisocyanate (MDI) is used as the hardener for the water-based adhesive. Add 10 grams of MDI to 80 grams of the base, stir evenly, and then it can be used. The wooden board is bonded according to the method described in SS-EN 205 (Adhesives-Wood adhesives for non-structural applications-Determination of tensile shear strength of lap joints), and mechanical tensile test specimens are prepared according to the provisions. After the tensile test specimens were completed, they were subjected to mechanical tensile tests according to the C4 standard of SS-EN 12765 (Classification of thermosetting wood adhesives for nonstructural applications), and the test results are shown in Table 1.
[0041] [Example 2] Take 10 grams of polyvinyl alcohol (PVA) aqueous solution (BP-05, 30% by weight, Changchun synthetic resin), add 20 grams of styrene butadiene rubber (SBR) resin (LBT04, Shenfeng special application materials), mix evenly and thoroughly, then add 50 grams of natural latex (60% by weight, made in Thailand), mix evenly and thoroughly to complete the base of the water-based adhesive. Use quaternary ammonium salt polymer (PAE, Changchun synthetic resin) as the hardener of the water-based adhesive, add 10 grams of PAE to 80 grams of the base, mix evenly and thoroughly to use. Adhere the wooden boards according to the method described in SS-EN 205 (Adhesives-Wood adhesives for non-structural applications-Determination of tensile shear strength of lap joints), and prepare mechanical tensile test specimens according to the provisions. After the tensile test specimens were completed, they were subjected to mechanical tensile tests according to the C4 standard of SS-EN 12765 (Classification of thermosetting wood adhesives for nonstructural applications), and the test results are shown in Table 1.
[0042] [Example 3] Take 50 grams of polyvinyl alcohol (PVA) aqueous solution (BP-05, 30% by weight, Changchun synthetic resin), add 20 grams of styrene butadiene rubber (SBR) resin (LBT04, Shenfeng special application materials), mix evenly and thoroughly, then add 10 grams of natural latex (60% by weight, made in Thailand) and 20 grams of calcium carbonate, and stir evenly and thoroughly to complete the base of the water-based adhesive. Diphenylmethane diisocyanate (MDI) is used as the hardener for the water-based adhesive, and 10 g of MDI is taken and added to 100 g of the base, and mixed well before use. Wood boards are bonded according to the method described in SS-EN 205 (Adhesives-Wood adhesives for non-structural applications-Determination of tensile shear strength of lap joints), and mechanical tensile test specimens are prepared according to the regulations. After the tensile test specimens were completed, they were subjected to mechanical tensile tests according to the C4 standard of SS-EN 12765 (Classification of thermosetting wood adhesives for nonstructural applications), and the test results are shown in Table 1.
[0043] [Example 4] Take 20 grams of polyvinyl alcohol (PVA) aqueous solution (BP-05 base 30% by weight, base, Changchun synthetic resin), add 50 grams of styrene butadiene rubber (SBR) resin (LBT04, base Shenfeng special application material), mix evenly and thoroughly, then add 10 grams of natural latex (60% by weight, base, made in Thailand) and 20 grams of calcium carbonate, and stir evenly and thoroughly to complete the base of the water-based adhesive. Diphenylmethane diisocyanate (base MDI) is used as the hardener for the water-based adhesive, take 10g of MDI, add it to 100g of base, and mix well before use. Adhesive the wooden boards according to the method described in SS-EN 205 (Adhesives-Wood adhesives for non-structural applications-Determination of tensile shear strength of lap joints), and prepare mechanical tensile test specimens according to the regulations. After the tensile test specimens were completed, they were subjected to mechanical tensile tests according to the C4 standard of SS-EN 12765 (Classification of thermosetting wood adhesives for nonstructural applications), and the test results are shown in Table 1.
[0044] [Comparative Example 1] Take 40 grams of styrene butadiene rubber (SBR) resin (LBT04 base material Shenfeng special application material), add 40 grams of natural latex (60 wt% base material made in Thailand) and 20 grams of calcium carbonate, and mix and stir evenly to complete the base material of the water-based adhesive. Use diphenylmethane diisocyanate (base material MDI) as the hardener of the water-based adhesive, add 10 grams of MDI to 100 grams of the base material, and mix well and evenly before use. Bond the wood boards according to the method described in SS-EN 205 (Adhesives-Wood adhesives for non-structural applications-Determination of tensile shear strength of lap joints), and prepare mechanical tensile test specimens according to the provisions. After the tensile test specimens are completed, perform mechanical tensile side tests according to the C 4 standard of SS-EN 12765 (Classification of thermosetting wood adhesives for nonstructural applications), and the test results are shown in Table 1.
[0045] [Comparative Example 2] Take 40 grams of polyvinyl alcohol (PVA) aqueous solution (BP-05 base 30% by weight, Changchun synthetic resin), add 40 grams of natural latex (60% by weight, made in Thailand) and 20 grams of calcium carbonate, and mix well to complete the base of the water-based adhesive. Diphenylmethane diisocyanate (MDI) is used as the hardener for the water-based adhesive, and 10 grams of MDI is added to 100 grams of the base, and then mixed well before use. The wood board is bonded according to the method described in SS-EN 205 (Adhesives-Wood adhesives for non-structural applications-Determination of tensile shear strength of lap joints), and mechanical tensile test specimens are prepared according to the provisions. After the tensile test specimens are completed, mechanical tensile side tests are performed according to the C 4 standard of SS-EN 12765 (Classification of thermosetting wood adhesives for nonstructural applications), and the test results are shown in Table 1.
[0046] Table 1 shows the adhesives and compositions prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 and 2, and the results of the adhesive strength tests.
[0047] [Table 1]
[0048] Please refer to Example 1 and Example 2. The wood board bonded with the water-based adhesive produced by using the formulation of Example 1 can pass the most stringent C4 standard. In Example 2, PAE is used as a hardener, and the strength of the wood board bonded with the water-based adhesive produced by using the formulation of Example 2 is slightly lower than that of Example 1, which uses MDI as a hardener, but still passes the C4 standard.
[0049] Please refer to Example 3. In the formulation of Example 3, the amount of polyvinyl alcohol added is increased. In addition, calcium carbonate is added to increase the solid content of the entire water-based adhesive. Thus, the bonding strength of the woodblock bonded with the water-based adhesive formulated in Example 3 is still not affected and passes the C4 standard.
[0050] Please refer to Example 4. The formulation of Example 4 improves the proportion of styrene butadiene rubber. Also, calcium carbonate is added to improve the total solid content of the water-based adhesive. In this way, the adhesive strength of the wood board bonded with the water-based adhesive produced using the formulation of Example 4 is still not affected and can pass the C4 standard.
[0051] Please refer to Comparative Example 1. The water-based adhesive prepared in Comparative Example 1 without adding polyvinyl alcohol showed a significant decrease in adhesive strength in a wet state when the wood board was bonded with the water-based adhesive prepared according to the formulation of Comparative Example 1, and did not pass the C4 standard.
[0052] Please refer to Comparative Example 2. Comparative Example 2 is a water-based adhesive prepared without adding styrene-butadiene rubber, and the adhesive strength of the wood board bonded with the water-based adhesive prepared according to the formulation of Comparative Example 2 in a wet state is significantly reduced, and it does not pass the C4 standard.
[0053] As described above, the water-based adhesive of the present invention does not use formaldehyde and uses natural renewable raw materials, effectively reducing dependency on petrochemical products. The raw material used in the present invention is natural latex, which is produced by blending rubber latex with an environmentally friendly and non-toxic water-soluble polymer and further mixing with an appropriate hardener. The water-based adhesive of the present invention provides wood and bamboo with excellent water resistance, bonding strength, and mechanical strength.
[0054] The above description is merely a preferred embodiment of the present invention, and is not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included within the scope of the present invention.
Claims
1. A water-based adhesive for application to wood and bamboo, the water-based adhesive comprising a base material composed of a water-soluble polymer, a synthetic rubber latex, and a natural latex, and a curing agent selected from an isocyanate or a quaternary ammonium salt polymer, the weight ratio of the base material to the curing agent being 200:1 to 1:1, the water-soluble polymer being polyvinyl alcohol and occupying 2-30 weight percent of the total solid content of the base material, the synthetic rubber latex being selected from the group consisting of styrene-butadiene rubber latex and styrene-butadiene rubber latex containing carboxylic acid functional groups, the synthetic rubber latex occupying 2-60 weight percent of the total solid content of the base material, and the natural latex occupying 5-90 weight percent of the total solid content of the base material, A water-based adhesive for application to wood and bamboo, characterized in that the quaternary ammonium salt polymer comprises one or more quaternary ammonium salt polymers, the quaternary ammonium salt polymer being polyaminoamide-epichlorohydrin (PAE).
2. The water-based adhesive for application to wood and bamboo as claimed in claim 1, characterized in that the weight ratio of the base agent to the hardener is from 100:1 to 10:
3.
3. 2. The water-based adhesive for application to wood and bamboo according to claim 1, wherein the water-soluble polymer accounts for 3 to 25% by weight of the total solid content of the base material.
4. 2. The water-based adhesive for use on wood and bamboo according to claim 1, wherein the hydrolysis mol % of the water-soluble polymer in the base material is 70 to 99.8%.
5. 2. The water-based adhesive for application to wood and bamboo according to claim 1, wherein the synthetic rubber latex accounts for 3 to 55% by weight of the total solid content of the base material.
6. 2. The water-based adhesive for application to wood and bamboo according to claim 1, wherein the natural latex accounts for 5 to 85% by weight of the total solid content of the base material.
7. 2. The water-based adhesive for application to wood and bamboo according to claim 1, wherein the natural latex accounts for 5 to 75% by weight of the total solid content of the base material.
8. 2. The water-based adhesive for application to wood and bamboo materials according to claim 1, characterized in that the natural latex is selected from the group consisting of at least one of epoxidized natural latex and deproteinized natural latex or a combination thereof.
9. The water-based adhesive for application to wood and bamboo according to claim 1, characterized in that the isocyanate comprises one or more isocyanates, the isocyanate being a compound or polymer thereof containing an isocyanate functional group.
Citation Information
Patent Citations
Adhesive used for laminated materials and preparation method of same
CN109401674A
Curing of aqueous high polymer-isocyanate based adhesive
JP1988189487A
Adhereing method
JP1995026209A
Adhesive for producing plywood and production of plywood by using the same
JP1998121021A
Highly water-resistant adhesive composition
JP2007077206A